PENGARUH KONTEN MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN PRODUK RAMAH LINGKUNGAN CONTURE (Studi Pengaruh konten di feed Instagram @Contureconcretelab) - Muhammad Hujjatul Ihram, (2023)
Changes in consumer behavior towards awareness of the impact of the products they use have resulted in increased market demand for products made from environmentally friendly materials. In this modern era, social media has become one of the platforms that influence people's behavior. Instagram in this case is one of the social media applications that also has a lot of influence on people's behavior. One company that consistently creates environmentally friendly products is Conture. Is a design studio company from Bandung that introduces material products with the basic ingredients of wood fiber from recycled cigarette butts. In this study, the authors used Cognitive Response theory. then for the type of quantitative data used is explanatory research which is a type of research conducted with the aim of understanding the impact of change. The amount of influence data from Instagram Social Media Content @contureconcretelab on Purchase Decisions for Conture Environmentally Friendly Products made from Utilizing Cigarette Butts Waste is 50%, while the remaining percentage is 50% which comes from external factors.